An approach toward novel bioactive natural products antroquinonols: de novo construction of the carbocyclic core. Issue 44 (28th October 2015) - Modugu, Nagi Reddy; Mehta, Goverdhan
Graphical abstract: Abstract: A new, short, approach toward bioactive antroquinonols has been conceptualized wherein the key carbocyclic core has been readily assembled employing disposable norbornyl scaffold as the regio- and stereo-director and a Wittig olefination based strategy is projected for appending the farnesyl arm.